معاملات المعاقين، مفهومها وضوابطها على ضوء النصوص الشرعية: دراسة تحليلية: Dealing with the People of disabilities, its concept and controls in the provision of Sharīa’: An analytical study - Sarafdeen Aminullah; Mohd. Afandi Bin Awang Hamat (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث قد ضمنت الشريعة الإسلامية لجميع الخلق عموما، وللإنسانية على وجه الخصوص؛ حياة طيبة وعيشة عادلة في كل الأحوال والأوقات، من خلال وضع الأحكام؛ التي تستنبط من النصوص الشرعية، والتي تدعو تغيرات الأحوال الإنسانية، والموجات العصرية إلى دراسة هذه النصوص الخاصة الواردة بشكل مباشر حول فقه حياة ذوي الإعاقات في المجتمعات، وإشكالية هذا البحث تنبع من: ظاهرة الهموم والمشكلات الأسرية، أو الاجتماعية عند وجود شيء من العجر والإعاقة في بعض أفراد المجتمع، أو إهمال ذوي الإعاقات من دون الاهتمام والرعاية، وكذلك قلة توعية المعاقين بحقوقهم في المجتمع في ضوء كتاب الله والسنة المطهرة. وتزويد ذلك مما يؤكد للناس جميعا أهمية هذه الفئة الخاصة عند التعاملات واندماجهم في المعاملات، وبالنظر فيها يستخرج بعض أحكام وضوابط التي ترشد إلى الاهتمام الجاد بهم، ومراعاتهم في المجتمع، وهذا يحل الكثير من الهموم والمشكلات الأسرية، والاجتماعية، ويظهر للناس جودة أحكام النصوص الشرعية من القرآن الكريم، والسنة المطهرة، والقواعد الفقهية وغيرها من أقوال العلماء في أصحاب ذوي الإعاقة والعجز، وقد سلك الباحثان المنهج الوصفي التحليلي، حيث أنه بيّن المراد بالإعاقة والمعاقين، ونصوص الشريعة الإسلامية، وأهمية دراستها ودورها في استباط الأحكام حول معاملات المعاقين، وتحليل أقوال العلماء فيها، وأبرز النتائج التي توصل إليها الباحثان هو: تضمين الحقوق وصونها للمعاقين في كونها أنها لم تكن أمرا تافئا التي يمكن أن يتلاعب الناس بها عموما، وبين المسلمين خصوصا، ومن نظر في أحوال المعاقين في هذه الحياة المعاصرة والتغييرات التي تحصل في العالم، يدرك أهمية هذه الدراسة وتأكيد ذلك ومطالبة المسؤولين بجميع ما لهؤلاء الفئة من الحقوق وإنذار الجهات المعنية بها، عند التلاعب والتساهل فيهم، ومن يراجع كتب التفسير وشروح الحديث يفهم من الشريعة الإسلامية حسن الاهتمام والتحضير والتكاتف والتكامل والرعاية، لجميع الخلق كافة. ABSTRACT: Shariah law has firmly guaranteed for all creation in general, and for humanity in particular, a good life and a standard living in all circumstances, through the establishment of rulings that are derived from the legal texts, which call for changes in human conditions and modern trends to study these specific texts that are directly related to the jurisprudence of the life of people with disabilities in societies. The problem of this research stems from: the phenomenon of harmful concerns and family or social problems when there is some disability or handicap in some members of society, or neglect of people with disabilities without being given any interest and proper care they deserve, as well as the lack of awareness of these disabled people of their own rights in the society in light of the holy book of Allah and the pure Sunnah of Prophet Muhamed (S.A.W). And providing that which confirms to all people the importance of this special category in any intrepersonal relationship or dealings, and their integration into all types of dealings, and by looking into it, some rulings and guidelies are extracted that guide to give a serious attention to them, and their consideration in society, and this will solve many unfortunate concerns and various problems within the family and society, and show people the quality of the rulings of the legal texts from the Holy Quran, the pure Sunnah, and the jurisprudential rules and other sayings of scholars regarding people with disabilities and incapacity. The researchers followed the descriptive and analytical approach, as it clarified what is meant by disability and the disabled people, and the uses of texts of Islamic law, and the importance of studying them and their role in deducing rulings on the dealings of these disabled people, and analyzing the sayings of scholars regarding them, and the most prominent results that the researchers reached are: including ability to identify the rights of people with disabilities and preserving them for them in which that they were not a trivial matter that people in general, and Muslims in particular, can manipulate. Whoever looks into the conditions of the disabled people in this contemporary life and the changes that are consitantly occuring in the world, will realizes the importance of this study and confirms it and this study also demands from officials all the rights that this category of people with disability have and warns the concerned parties, when they manipulate and lenient with them, and whoever reviews the books of interpretation (Tafsir) and explanations of the hadith (Shuruhu) understands that Islamic law really requires good care, preparation, solidarity, integration and care for all creation.